Neurohormonal Blockade During Left Ventricular Assist Device Support. Issue 8 (August 2020) - Imamura, Teruhiko; Mehta, Priya; Nguyen, Ann; Chung, Ben; Narang, Nikhil; Rodgers, Daniel; Raikhelkar, Jayant; Smith, Bryan; Song, Tae; Ota, Takeyoshi; Jeevanandam, Valluvan; Kim, Gene; et al.
Abstract : Neurohormonal blockade (NHB) is the mainstay of therapy for patients with systolic heart failure (HF). However, the efficacy in patients with left ventricular assist devices (LVADs) remains unknown. Of all, 114 LVAD patients (57 [48, 65] years old and 78% male) were enrolled and followed during the early period (6 months after index discharge), and 98 were followed during the late period (6–12 months following index discharge). Of them, 46% were on beta-blocker (BB), 49% on angiotensin-converting enzyme inhibitor (ACEi) and/or angiotensin II receptor blocker (ARB), and 51% on aldosterone antagonist at baseline. Prevalence of BB and ACEi/ARB use increased during the study period. During the early period, similar event rates were found irrespective of the NHB uses. During the late period, BB was associated with reduced HF readmission, and ACEi/ARB was associated with reduced HF readmission and gastrointestinal bleeding ( p < 0.05 for all). In conclusion, BB and ACEi/ARB use during the late period was associated with a reduction in HF recurrence in LVAD patients. Further prospective randomized control trials are warranted to clarify the utility of NHB therapy in LVAD patients. Abstract : Supplemental Digital Content is available in the text.